Olfactory Sensory Activity Modulates Microglial-Neuronal Interactions during Dopaminergic Cell Loss in the Olfactory Bulb - Grier, Bryce D.; Belluscio, Leonardo; Cheetham, Claire E. J. (Frontiers in Cellular Neuroscience, 2016)
The mammalian olfactory bulb (OB) displays robust activity-dependent plasticity throughout life. Dopaminergic (DA) neurons in the glomerular layer (GL) of the OB are particularly plastic, with loss of sensory input rapidly reducing tyrosine hydroxylase (TH) expression and dopamine production, followed by a substantial reduction in DA neuron number. Here, we asked whether microglia participate in activity-dependent elimination of DA neurons in the mouse OB. Interestingly, we found a significant reduction in the number of both DA neurons and their synapses in the OB ipsilateral to the occluded naris (occluded OB) within just 7 days of sensory deprivation. Concomitantly, the volume of the occluded OB decreased, resulting in an increase in microglial density. Microglia in the occluded OB also adopted morphologies consistent with activation. Using in vivo 2-photon imaging and histological analysis we then showed that loss of olfactory input markedly altered microglial-neuronal interactions during the time that DA neurons are being eliminated: both microglial process motility and the frequency of wrapping of DA neuron somata by activated microglia increased significantly in the occluded OB. Furthermore, we found microglia in the occluded OB that had completely engulfed components of DA neurons. Together, our data provide evidence that loss of olfactory input modulates microglial-DA neuron interactions in the OB, thereby suggesting an important role for microglia in the activity-dependent elimination of DA neurons and their synapses.